The Application of Yoga Pranayama and Gym Ball Exercise on Labor Pain During Active Phase at Pmb Desa Blahkiuh, Abiansemal, Badung - Widiastini, Luh Putu; Karuniadi, I Gusti Agung Manik (Journal of A Sustainable Global South; Vol 4 No 1 (2020): February 2020DO - 10.24843/jsgs.2020.v04.i01.p07, 2020)
Pain Labor is a physiological and individual experience. The cause of pain in labor is a combination of ischemia (hypoxia) the muscles of the uterus and stretching that occurs in the lower segment of the uterus (then the cervix). Non-pharmacological efforts that can be done in reducing pain in the mother in the face of labor are through the Application of Yoga Pranayama and Gym Ball Exercise. The purpose of this study was to determine the effect of the application of Yoga Pranayama and Ball Exercise Gym on Labor Pain Active Phase in PMB Blahkiuh Village, Abiansemal, Badung. This research method used the Quasi Experimental Design study with Nonequivalent Control Group Design. The approach used is a prospective approach. Sample consisted 40 respondents. Respondent selected by purposive sampling and divide into control group and intervention group. Respondents in intervention group were given Yoga Pranayama and Gym Ball Exercise, while in the control group respondents were given conventional therapy. The data were analyzed using the Paired T-test to compare the results of the pre-test and post-test, and to compare intervention and control groups use Independent T-Test. Based on statistical tests obtained all p values <0.05 means that there is a significant difference between pain labor in the control and intervention group, so it can be interpreted that pain scale in intervention group is lower than control group. The conclusion of this study was there’s influence on the application of Yoga Pranayama and the Ball Exercise Gym on Labor Pain in the Active Phase in PMB Blahkiuh Village, Abiansemal, Badung. Index Terms — labor pain, active phase, yoga pranayama, gym ball exercise